Managerial Features of the Municipal Educational System in Russia - Fedorova, Svetlana N.; Kartashova, Elena P.; Mukhametshina, Rezeda F.; Zalomnova, Svetlana P.; Ignatyev, Sergey V.; Kurushin, Victor V.; Davydova, Tatyana V.; Alenina, Elena E. (International Review of Management and Marketing, 2016)
The relevance of the paper is reasoned by the redistribution of powers and responsibilities in the field of education between the federal, regional and municipal authorities. There are preschool, secondary, secondary special and higher educational institutions, the establishments of additional, post-graduate education, institutions of retraining and professional development of different forms of ownership and administrative subordination (federal, regional, municipal) on the territory of the municipality. The purpose of the paper is to reveal managerial features of the municipal educational system in Russia. The leading method is the method of action research (AR), allowing to obtain new knowledge about the management of municipal educational system, identify strategies and trends of development of municipal educational system. The article reveals the essence of municipal educational system as a sustainable and systematic cooperation of educational institutions on the territory of the municipality, as well as local government and education authorities, providing a highly efficient organization of educational services and the able to self-preservation and development through self-organization and self-government. Strategies (building on the territory of the municipal district of a unified educational environment, the development of mechanisms of state and public management, the creation of innovative organizational and managerial mechanisms of inter-corporate cooperation of educational institutions) and trends (the formation of educational complexes of different types, the establishment of an adaptive managerial mechanism, development of municipal system of measuring and evaluating of education's quality, the creation of an integrated provision of municipal educational system's development) for the development of municipal educational system are identified and scientifically justified. Paper Submissions can be useful for research and teaching staff of the municipal educational system, experts of education authorities and regional authorities. Keywords: Municipal Educational System, State and Public Management, Education, Inter-Corporate Cooperation. JEL Classifications: A20, I21, I28